Majlis Sanggar Sanjung 2024 / Nor Azliana Norli - Norli, Nor Azliana (Faculty of Pharmacy, 2024)
On 12th July 2024, a Sanggar Sanjung Ceremony (Majlis Sanggar Sanjung) was held to acknowledge the achievements and contributions of the staff of Faculty of Pharmacy, UiTM to the university. This ceremony was conducted at the Pavilion Hall with the staff wearing beautiful outfits that suited the retro theme.